(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A microgrid is the combination of Distributed generators that interconnected with the main grid to ensure continuity in supply to the load. The operating system will be in grid-connected and the island mode. This paper presents a mathematical model of hybrid microgrid consisting of PV system, wind power generation using DFIG which are integrated to the utility grid and a PI Controller for controlling the transition from grid-connected mode to island mode and normal operation, each DG inverter sated in constant current control mode to provide preset power to the main grid. When it disconnects from the main grid each DG inverter detects and connect to voltage control mode in the islanding situation. The modeling is performed in MATLAB Simulink and results are discussed out to verify the operation of the proposed system